A CONCEPT FOR THE INTERNATONAL MONEY UNDER THE CIRCUMSTANCES OF THE GLOBAL FINANCIAL CRISIS - Jurek, Michał (Ekonomia i Prawo. Economics and Law, 2010)
The purpose of this article is to analyze, whether and to what extent a global financial turmoil, initiated with the U.S. subprime crisis, can provide a stimulus towards a creation of the new international money. A reduction of the dollar’s share in the official foreign exchange reserves is considered to be a first step in order to achieve this goal. Following issues are examined in the article: 1) the possibility of granting the unit of account of the IMF – SDR – the status of the main reserve currency; 2) the possibility of the fall of the dollar’s share in the official foreign exchange reserves of the IMF’s members in favor of other currency. Conducted research supports the view that these scenarios can become reality. However, this depends to the highest degree on the stand of the Asian countries on this matter. These very countries create very strong demand for the American securities, helping keep the dollar dominant.